The Influence of Customer Experience, Brand Trust, and Brand Awareness on Skintific Purchasing Decisions - Zalsabila Septiana Murbiyanti; Tatik Mulyati; Novy Rachma Herawati; Samsu Anhari Faujianto; Thea Ocktavia Putri (Pattimura University, 2026)
This study examines the influence of customer experience, brand trust, and brand awareness on purchasing decisions for Skintific beauty products in Madiun City. The aim is to determine how these three variables influence consumer purchasing decisions. The method used is quantitative with data collection through questionnaires completed by 100 respondents who use Skintific products, taken using a simple random sampling technique using the Slovin formula. Data analysis was carried out through classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing. The results show that customer experience, brand trust, and brand awareness partially and simultaneously have a significant influence on purchasing decisions for Skintific products in Madiun City. The implications of this study emphasize the importance of companies in paying attention to customer experience, building brand trust, and increasing brand awareness to improve consumer purchasing decisions and maintain product competitiveness in the beauty market. Marketing strategies that integrate these three aspects can strengthen Skintific's position in the competitive beauty industry.